ATF3 controls proliferation of osteoclast precursor and bone remodeling - Fukasawa, Kazuya (Sci Rep, 2016)
Bone homeostasis is maintained by the sophisticated coupled actions of bone-resorbing osteoclasts and bone-forming osteoblasts. Here we identify activating transcription factor 3 (ATF3) as a pivotal transcription factor for the regulation of bone resorption and bone remodeling under a pathological condition through modulating the proliferation of osteoclast precursors. The osteoclast precursor-specific deletion of ATF3 in mice led to the prevention of receptor activator of nuclear factor-κB (RANK) ligand (RANKL)-induced bone resorption and bone loss, although neither bone volume nor osteoclastic parameter were markedly altered in these knockout mice under the physiological condition. RANKL-dependent osteoclastogenesis was impaired in vitro in ATF3-deleted bone marrow macrophages (BMM). Mechanistically, the deficiency of ATF3 impaired the RANKL-induced transient increase in cell proliferation of osteoclast precursors in bone marrow in vivo as well as of BMM in vitro. Moreover, ATF3 regulated cyclin D1 mRNA expression though modulating activator protein-1-dependent transcription in the osteoclast precursor, and the introduction of cyclin D1 significantly rescued the impairment of osteoclastogenesis in ATF3-deleted BMM. Therefore, these findings suggest that ATF3 could have a pivotal role in osteoclastogenesis and bone homeostasis though modulating cell proliferation under pathological conditions, thereby providing a target for bone diseases.